Novel Perspectives of Stem Cell Manufacturing and Therapies - Kitala, Diana; Colette Maurício, Ana (IntechOpen, 2021)
In the 1950s, Nobel Prize winner Dr. E. Donnall Thomas was the first to successfully transplant hematopoietic stem cells. Since then, studies on stem cells have evolved and expanded worldwide. There are more than 650,000 scientific publications on stem cells and more than 8000 stem cell clinical trials. This book summarizes types of stem cells, key studies, ongoing trials, and future perspectives. It also includes ethical, formal, and legal aspects to give the reader a comprehensive view of the field.